The effects of L-NAME on DU145 human prostate cancer cell line: A cytotoxicity-based study. (February 2020) - Kacar, S; Kar, F; Hacioglu, C; Kanbak, G; Sahinturk, V
Of all cancer types, prostate cancer is the second most common one with an age-standardized incidence rate of 29.3 per 100, 000 men worldwide. Nitric oxide (NO) is both a radical and versatile messenger molecule involved in many physiological activities. NO was documented to be highly secreted and utilized by cancer cells. N ω -nitro-L -arginine methyl ester (L-NAME) is utilized for inhibiting NO synthase. Its worst long-term side effect is reported to be hypertension, hence less cytotoxic than chemotherapeutic agents. Herein, we carried out a cytotoxicity study on how different doses of L-NAME affect DU145 human prostate cancer cells. First, toxic doses of L-NAME were determined. Then, while antioxidant capacity was determined by glutathione and total antioxidant status, oxidative stress was evaluated by quantifying malondialdehyde, NO, and total oxidant status levels. Inflammatory effects of L-NAME were investigated by measuring tumor necrosis factor- α and interleukin-6 (IL-6) levels. Apoptotic effects of L-NAME were evaluated by measuring cytochrome C somatic and caspase 3 levels and by staining Bax protein. Finally, morphological analysis was performed. IC50 of L-NAME against DU145 cells was 12.2 mM. In L-NAME-treated DU145 cells, a dose-dependent increase in oxidative stress, inflammatory, and apoptotic marker proteins and decrease in antioxidant capacity were observed. While at the moderate dose of L-NAME, apoptotic changes were commonly observed, at higher doses, vacuolated and swollen cells were also recorded. We believe that the present study will encourage future studies by providing insights about dose and effects of L-NAME.